Using PQRST Strategy and Powtoon Media To Improve Students’ Reading Engagement - Pratidina Parameswari; Ikhsanudin Ikhsanudin; Zainal Arifin (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
The main objective of this research was to find out the improvement of students’ engagement in reading comprehension of descriptive text using PQRST Strategy and PowToon media to the seventh grade students of SMP Negeri 3 Sungai Raya in academic year 2019/2020. This classroom research was conducted in three cycles. The subject of this research was 32 students in class VII E. The researcher used observation checklist, field notes and reading tests as tools of data collection. The improvement of students’ engagement improvement could be seen was reflected byfrom their students’ performance in the teaching and learning process. The students became more enthusiastic in following participating in the lesson because they worked in group with their friends. The teacher gave a PQRST learning log to each groups as a guide during the stage of PQRST strategy shown in PowToon media. Preview, the students guess the topic by read the title and the pictures. Question, the students made questions based on they were interested in Preview stage. Read, the students read the whole text while looking for the answers of their own questions, they also wrote the difficult words found. State, the teacher and the students discussed about the contents of the text and the difficult words. The students have also take turn presented the results of their group’s work with their own words. Last in Test the teacher gave the students multiple choice to make sure they understood the text clearly. Those activities make students more active during the class, so their reading engagement was improved.